Evaluation of chromosome aberrations, sister chromatid exchange and micronuclei in patients with type-1 diabetes mellitus - Cinkilic, Nilüfer; Kiyici, Sinem; Celikler, Serap; Vatan, Ozgur; Oz Gul, Ozen; Tuncel, Ercan; Bilaloglu, Rahmi (Mutation research, 2009)
Oxidative stress-induced DNA damage seems to play a role in the pathogenesis of type-1 diabetes mellitus and its complications. Several in vitro assays have been used to measure the DNA damage produced by oxidative stress. In the present study, we aimed to investigate the frequency of sister chromatid exchange (SCE), chromosomal aberrations (CA) and micronuclei (MN) in type-1 diabetes mellitus patients compared with healthy controls. SCE, CA and MN tests were carried out with the blood-cell cultures from 35 type-1 diabetic patients and 15 healthy, age- and sex-matched control subjects. The mean age of the type-1 diabetic patients was 31.89 ± 10.01 years, with a mean duration of the diabetes of 7.8 ± 6.02 years. The mean level of HbA1c of the type-1 diabetic patients was 8.37 ± 1.36%. Only three (8.5%) patients with type-1 diabetes mellitus had an HbA1c level below 7%. Patients with type-1 diabetes mellitus showed a higher frequency of SCE compared with controls (5.44 ± 1.47 and 2.54 ± 0.82, respectively, p < 0.001), but there was no significant correlation between the duration of diabetes, HbA1c and SCE. No significant difference was found in CA or MN frequency in type-1 diabetic patients compared with controls. In conclusion, these results suggest that type-1 diabetes mellitus is a condition with genomic instability characterized by an increased level of SCE. Hyperglycemia-induced oxidative stress may be the underlying factor of the increased SCE frequency.